Too Much of a Good Thing? Self-Esteem and Latinx Immigrant Youth Academic Achievement. Issue 3 (August 2018) - Lew, Shim; Harklau, Linda
Self-esteem is often invoked in scholarly literature and popular belief alike as contributing positively to academic achievement in immigrant youth. Yet, research exploring this link is sparse and findings are mixed. This article reports on a 5-year-long ethnographic case study exploring the educational path of a college-bound Latino adolescent in one southeastern U.S. new immigrant community in which the student's high self-esteem appeared to have a negative influence on academic achievement. The study traces how high self-esteem caused the student to disregard negative feedback regarding his academic performance and focus his attention instead on excelling in extracurricular pursuits, particularly athletics. The study also finds that educators gave mixed messages about achievement that reinforced the student's high self-esteem but contributed to low academic expectations and outcomes. In all, it suggests the need to reexamine the assumed link between high self-esteem and academic achievement in immigrant youth and to consider individual differences.